PENGUATAN KECERDASAN DIGITAL PEMUDA SEBAGAI BENTUK KETERLIBATAN DALAM TOTAL DIPLOMASI INDONESIA - Christy Damayanti; Andika Drajat Murdani (Adi Widya : Jurnal Pengabdian Masyarakat, 2020)
The digital age encourages the flow of information to move quickly and shift the pattern of international relations. This has influenced the development of the total diplomacy scheme in supporting the achievement of Indonesia's diplomacy goals. In this program, we take international relations students of Slamet Riyadi University as activity partners.International Relations students should be able to engage in total diplomacy positively. They will be provided with digital intelligence according to the positive character of the nation is needed, so that they are able to contribute in growing Indonesia's positive image in the international eyes. This community service program would like to support Indonesia's efforts to collaborate digital media in a total diplomacy scheme with student youth agents, through "Strengthening Youth Digital Intelligence as a Form of Its Contribution to Indonesian Total Diplomacy." They were given socialization, training and assistance in creating content related to diplomacy. The series of activities lasted for six months, starting from the exploration to the distribution of video content made by them which was adjusted to the Indonesian diplomacy mission. Keyword : digital intelligence, Indonesia, total diplomacy, youth